2017
DOI: 10.5334/ijic.3096
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Integrated Care for People with Chronic Conditions: Key Findings from EU FP-7 Project INTEGRATE and Beyond

Abstract: Background:Political and public health leaders increasingly recognize the need to take urgent action to address the problem of chronic diseases and multi-morbidity. European countries are facing unprecedented demand to find new ways to deliver care to improve patient-centredness and personalization, and to avoid unnecessary time in hospitals. People-centred and integrated care has become a central part of policy initiatives to improve the access, quality, continuity, effectiveness and sustainability of healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 91 publications
1
47
1
1
Order By: Relevance
“…Ultimately, however, the implemented improvement activities mainly targeted collaboration, as the initial aim of improving person‐centredness of care delivery appeared to be unfeasible. Previous studies suggest that communication, understanding and trust are important prerequisites for interprofessional collaboration (Borgermans et al, ; Mulvale, Embrett, & Razavi, ; Xyrichis & Lowton, ), and are part of a transformational process that needs to be established before one can change actual care delivery processes (Manojlovich et al, ). This could explain why activities targeting person‐centredness were not in line with professionals' needs at the time of the improvement process; these activities targeted the care delivery process, whereas the prerequisites for interprofessional collaboration still needed to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, however, the implemented improvement activities mainly targeted collaboration, as the initial aim of improving person‐centredness of care delivery appeared to be unfeasible. Previous studies suggest that communication, understanding and trust are important prerequisites for interprofessional collaboration (Borgermans et al, ; Mulvale, Embrett, & Razavi, ; Xyrichis & Lowton, ), and are part of a transformational process that needs to be established before one can change actual care delivery processes (Manojlovich et al, ). This could explain why activities targeting person‐centredness were not in line with professionals' needs at the time of the improvement process; these activities targeted the care delivery process, whereas the prerequisites for interprofessional collaboration still needed to be established.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of such a facilitator is also dependent on their credibility, authority and a supportive environment (Rycroft‐Malone et al, ). Finally, developing and implementing tangible improvements to integrated care requires commitment from stakeholders on multiple levels, since sustainable improvements need adjustments on the operational, managerial and administrative levels of the health and social care systems (Borgermans et al, ; Mulvale et al, ). Our study showed that, as the improvement activities narrowed and became more pragmatic, professionals became more committed to the improvement process while the steering group members' commitment and engagement decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests a paradigm shift from the traditional practitioner-led management which interprets the management of a disease isolated and distinct from a person's perspective, experience, and expectation. 29 PCOS affects individual women differently and varies throughout the lifespan. 3,30 The priorities of every woman with PCOS facing multiple demanding health problems differ and may change with time.…”
Section: Patient-centered Care Addressing the Biopsychosocial Dimensionsmentioning
confidence: 99%
“…Reviews of evidence consistently highlight management as either an enabler or barrier to successful implementation of integrated care [1][2][3][4]54]. This includes management at both strategic and operational levels [5].…”
Section: Introductionmentioning
confidence: 99%